Determining the Effect of Core Strength Training on Dynamic Balance, Flexibility and Footwork Skill of Badminton Players - Farooque Sm; Sharina Naorem; Ahsan Huda Yumkhaibam; Amit Dhar; Mukesh Mitra; Prasanta Kumar Das (Physical Education Theory and Methodology)
Background. Badminton is a technical racket sport that requires intense and explosive movements, with performance dependent on factors such as balance, agility, and core strength. Previous research has emphasized the significance of core fitness in fostering stability and dynamic balance for performance and injury prevention. However, its effects on badminton-specific skills remain relatively underexplored.